2021
DOI: 10.1177/2151459321992742
|View full text |Cite
|
Sign up to set email alerts
|

Can We Stratify Quality and Cost for Older Patients With Proximal and Midshaft Humerus Fractures?

Abstract: Introduction: This study sought to investigate whether a validated trauma triage tool can stratify hospital quality measures and inpatient cost for middle-aged and geriatric trauma patients with isolated proximal and midshaft humerus fractures. Materials and Methods: Patients aged 55 and older who sustained a proximal or midshaft humerus fracture and required inpatient treatment were included. Patient demographic, comorbidity, and injury severity information was used to calculate each patient’s Score for Traum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…However, the point estimates of the odds ratio significantly increased as the risk level increased. Earlier studies have reported similar dose-response patterns when either high-or low-energy STTGMA scores were used to assess the occurrence of complications and length of stay among older patients with tibial shaft and plateau fractures, 21 midshaft humeral fractures, 23 hip fractures, 36 and ankle fractures. 37 Our study has added to the growing body of literature on the diagnostic accuracy of the STTGMA in predicting the clinical trajectory among middle age and older adults involved in motor vehicle crash injuries.…”
Section: Discussionmentioning
confidence: 83%
“…However, the point estimates of the odds ratio significantly increased as the risk level increased. Earlier studies have reported similar dose-response patterns when either high-or low-energy STTGMA scores were used to assess the occurrence of complications and length of stay among older patients with tibial shaft and plateau fractures, 21 midshaft humeral fractures, 23 hip fractures, 36 and ankle fractures. 37 Our study has added to the growing body of literature on the diagnostic accuracy of the STTGMA in predicting the clinical trajectory among middle age and older adults involved in motor vehicle crash injuries.…”
Section: Discussionmentioning
confidence: 83%
“…16 Furthermore, the model's predictive ability has also been validated in several other patient populations such as hip, femur, and humerus fracture patients. [10][11][12][13][14] In the clinical setting, the STTGMA tool has the potential to aid clinicians in providing more value-based care. 10,14,15,17 Healthcare providers can use the score early in a patient's admission to gain insight into what the trajectory of the patient's hospital course may look like.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] In the clinical setting, the STTGMA tool has the potential to aid clinicians in providing more value-based care. 10,14,15,17 Healthcare providers can use the score early in a patient's admission to gain insight into what the trajectory of the patient's hospital course may look like. Using risk groups similar to the ones used in this study, clinicians can triage patients into more cost-effective standardized care pathways based on their risk group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations